Guilt: a force of cultural transformation - Kellenbach, Katharina von; Buschmeier, Matthias (Oxford University Press, 2022)
Since the end of the 20th century, social movements around the world have called for accountability and reparation for past harms, particularly harms committed by states against various minority groups. This volume argues that guilt is a productive force that helps to balance unequal power dynamics between individuals and groups. With chapters bridging the social sciences, law, and humanities, chapter authors examine the role and function of guilt in society and present case studies from seven national contexts.
Keywords: Moralpsychologie; Scham; Schuld